HomeCoRe for Telerehabilitation in Mild or Major Neurocognitive Disorders: A Study Protocol for a Randomized Controlled Trial - Bernini, Sara; Panzarasa, Silvia; Sinforiani, Elena; Quaglini, Silvana; Cappa, Stefano F.; Cerami, Chiara; Tassorelli, Cristina; Vecchi, Tomaso; Bottiroli, Sara (Frontiers in Neurology, 2021)
Background: Given the limited effectiveness of pharmacological treatments for cognitive decline, non-pharmacological interventions have gained increasing attention. Evidence exists on the effectiveness of cognitive rehabilitation in preventing elderly subjects at risk of cognitive decline and in reducing the progression of functional disability in cognitively impaired individuals. In recent years, telerehabilitation has enabled a broader application of cognitive rehabilitation programs. The purpose of this study is to test a computer-based intervention administered according to two different modalities (at the hospital and at home) using the tools CoRe (Cognitive Rehabilitation) and HomeCoRe, respectively, in participants with Mild or Major Neurocognitive Disorders. Method: Non inferiority, single-blind randomized controlled trial where 40 participants with Mild or Major Neurocognitive Disorders will be assigned to the intervention group who will receive cognitive telerehabilitation through HomeCoRe or to the control group who will receive in-person cognitive intervention through CoRe, with the therapist administering the same computer-based exercises. The rehabilitative program will last 6 weeks, with 3 sessions/week, each lasting approximately 45 minutes. All participants will be evaluated on an exhaustive neuropsychological battery before (T0) and after (T1) the intervention; follow-up visits will be scheduled after 6 (T2) and 12 months (T3). Discussion: The results of this study will inform about the comparability (non-inferiority trial) of HomeCoRe with CoRe. Their equivalence would support the use of HomeCoRe for at distance treatment, favoring the continuity of care. Ethics and dissemination: The study has been approved by the Local Ethics Committee and registered in https://clinicaltrials.gov (NCT04889560). The dissemination plan includes the scientific community through publication in open-access peer-reviewed scientific journals, and presentations at national and international conferences.